Study of Clinical and Biochemical Parameters of Type 2 Diabetic Subjects with Pulmonary Tuberculosis - Afsana, F; Jamil, SNAA; Latif, ZA (BIRDEM Medical Journal, 2014)
Aims: Type 2 DM is a global epidemic and recognized as a threat to pulmonary tuberculosis (PTB) control worldwide especially in developing countries. When tuberculosis is diagnosed in diabetic subjects both can be affected in term of clinical presentation and course of disease. The aim of the study was to evaluate the demographic, clinical and biochemical parameters of newly detected PTB patients with type 2 diabetes. Methods: Seventy two diabetic subjects with newly detected PTB attending outpatient department, BIRDEM were studied. Patients with fever, cough, hemoptysis and/or weight loss were interviewed by a structured questionnaire. After thorough clinical examination, blood sugar, complete blood count (CBC), ESR, sputum for bacteriological culture and acid fast bacilli (AFB) (3 samples), X-ray chest were done. The diagnosis of PTB was based on a positive sputum AFB test, a suggestive CBC report or typical radiographic findings with high clinical probability. Diagnosed PTB cases were included in the study. All patients were followed up at least at1st, 3rd and 6th month of antitubercular therapy. Result: Mean age of study subjects was 46(19-75) years. The study subjects do not have past history of tuberculosis. Most of the study subjects (98.6%) were on insulin for treatment of diabetes. Mean body mass index (BMI) was 19.9kg/m². Mean ESR (mm in 1st hour) was 94.5 with 60% subjects having ESR >100. Sputum for bacteriological culture revealed no growth in 77.3% patients. Chest X-ray revealed cavity in 47.2%, opacity in 40.3%, both opacity and cavity in 5.6 %, pleural effusion in 5.6% and 5.5% had no detectable lesion. All patients were sputum AFB positive and among them 73.6% (n=53) had AFB positive in all 3 samples. Most of the patients (n=62, 86.6%) become sputum AFB negative after one month of treatment initiation. Rest 10 subjects (13.4%) become sputum negative in 2 months follow up and all of these patients had cavitary lesions in chest X-rays. A good number of the patients (98%) with positive x-ray finding showed radiological improvement after 2 months of antitubercular treatment. All the patients completed their therapy without any interruption for 6 months. Conclusion: Pulmonary cavity and opacity is the commonest radiological finding among study subjects. Sputum positivity for AFB is a good diagnostic tool for PTB in diabetic subjects. Subjects with cavitary lesion in chest X-ray become sputum negative than others. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18545 Birdem Med J 2014; 4(1): 5-8